Factors associated with acute kidney injury in surgical patients at the intensive care unit - Benichel, Cariston Rodrigo [UNESP]; Meneguin, Silmara [UNESP] (Univ Federal Ceara, Dept Enfermagem, 2018)
Objective: to analyze factors associated with acute kidney injury in surgical patients at the intensive care unit. Methods: case-control study including survey of patient history records and a sample of 246 patients. For the differences of proportions and means, the chi-squared and Student's t-test were used, respectively. The association between variables was verified by means of univariate and later multivariate analyses with logistic regression. The odds ratio was used as an effect measure and significance was set at 5%. Results: the main associated factors were: period of hospitalization, gastrointestinal etiology, mechanical ventilation, sepsis, hypovolemia, arrhythmia, furosemide, vasopressors, simultaneous antibiotics and concomitant occurrence of more than three factors. Conclusion: acute kidney injury represented a systemic event, affected patients of advanced age who were hospitalized longer and predisposed to death. It was associated with gastrointestinal etiologies, problems, nephrotoxic drugs and concomitant factors that contribute to increase the risk of its development.
Keywords: Acute Kidney Injury; Risk Factors; Critical Care; Case-Control Studies